ANALYSIS OF SUPPORTING FACTORS ON READINESS FOR CHANGE AT PT PLN (PERSERO) SUMATERA BARAT - Robby Prakoso; Harif Amali Rivai; Hendra Lukito (Jurnal Mantik, 2022)
The aim of this study is to analyze the supporting factors that influence readiness for change, including employee engagement and resistance to change with perceived organizational support as a mediating variable. Transformation is the biggest problem facing all organizations today and the challenge lies in employees needing to be prepared for organizational change. The population in this study were employees of PT PLN (Persero) Unit Induk Wilayah Sumatera Barat with a sample of 179 employees. The analytical method used is descriptive statistical analysis and factor description analysis using SmartPLS 3.0. The results of the study indicate that employee engagement has a positive and significant effect on perceived organizational support; resistance to change has no effect on perceived organizational support; employee engagement and perceived organizational support have a positive and significant influence on readiness for change; resistance to change has a negative and significant effect on readiness to change; Then perceived organizational support as a mediating variable only affects employee engagement with readiness for change.